1982
DOI: 10.2307/1541506
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGICAL AND BEHAVIORAL IDENTIFICATION OF THE SENSORY STRUCTURES MEDIATING PHEROMONE RECEPTION IN THE BLUE CRAB,CALLINECTES SAPIDUS

Abstract: Scanning electron microscopy was used to survey the aesthetasc tuft on the outer flagellum of the antennule (1st antenna) in order to identify sensilla potentially involved in pheromone detection by the male blue crab. These studies showed that the tuft of each antennule is divided into a mesial and lateral half by a region of cuticle from which no sensilla arise. Two setal types were revealed: the aesthetascs and previously undescribed sensilla which originate exclusively on the mesial side of the tuft and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 16 publications
1
71
0
Order By: Relevance
“…Bioassay-guided fractionation using a behavioural assay with adult male crabs showed that the sex pheromone of pubertal premoult females, which is the sexual stage, is one or more molecules that are small and polar. Both the <500 Da fraction and the 500-1000 Da fraction of urine of pubertal premoult females evoked male courtship stationary paddling, a distinctive behaviour elicited by the sex pheromone of females (Gleeson, 1980;Gleeson, 1982;Gleeson, 1991;Kamio et al, 2008). Fractions of urine of males did not evoke courtship stationary paddling.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bioassay-guided fractionation using a behavioural assay with adult male crabs showed that the sex pheromone of pubertal premoult females, which is the sexual stage, is one or more molecules that are small and polar. Both the <500 Da fraction and the 500-1000 Da fraction of urine of pubertal premoult females evoked male courtship stationary paddling, a distinctive behaviour elicited by the sex pheromone of females (Gleeson, 1980;Gleeson, 1982;Gleeson, 1991;Kamio et al, 2008). Fractions of urine of males did not evoke courtship stationary paddling.…”
Section: Discussionmentioning
confidence: 90%
“…ORNs in aesthetasc sensilla on the lateral flagellum of the antennules of crustaceans are known to uniquely detect conspecific chemicals associated with sex, social interactions and alarm (Aggio and Derby, 2011;Schmidt and Mellon, 2011;Breithaupt and Thiel, 2011), including courtship pheromones of blue crabs (Gleeson, 1982;Gleeson, 1991). Our observation, from Ca 2+ imaging, that NAGL activates these ORNs is consistent with NAGL being a candidate intraspecific signal, NAGL is excreted or secreted into urine and detected by olfactory receptor neurons of male Shown is the pathway for the biosynthesis and degradation of chitin (Horst et al, 1993;Muzzarelli, 1996;Merzendorfer and Zimoch, 2003), and a proposed role for NAGL in this pathway.…”
Section: Research Articlementioning
confidence: 99%
“…The lateral filament of the short antennule of a C. sapidus (Fig.1C) is only 2mm in length (Fig.1D) and bears a dense tuft of approximately 650-700 aesthetascs (Gleeson, 1982) on its ventral surface. The aesthetascs are 700-1000m in length and 10-12m in diameter (Gleeson, 1982).…”
Section: Olfactory Antennules and Sniffing By Crustaceansmentioning
confidence: 99%
“…The aesthetascs are 700-1000m in length and 10-12m in diameter (Gleeson, 1982). Analysis of high-speed videos of C. sapidus antennules shows that they flick the lateral filament at a rate of 3Hz, and that during the flick downstroke, the aesthetasc tuft sweeps through an arc of 113deg, moving only a short linear distance (0.40cm) at a velocity of 0.1ms -1 (M. Martinez, U. Lee, and M.A.R.K., unpublished).…”
Section: Olfactory Antennules and Sniffing By Crustaceansmentioning
confidence: 99%
“…Aesthetascs alone mediate the responses to intraspecific chemicals (Johnson and Atema, 2005;Horner et al, 2008;Shabani et al, 2008). In crabs, the aesthetascs also mediate responses to intraspecific signals such as sex pheromones (Gleeson, 1982;Gleeson, 1991). The antennules of crabs play a somewhat different role in chemo-orientation, although ablation of the antennules slows the crabs' upstream progress (Keller et al, 2003;Dickman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%